Reconstruction of relative permittivity and thickness profiles of different dielectric samples using time domain multiple reflection method - Aman; Singh V.; Bhattacharyya S. (My University, 2025)
In this paper, a novel method involving multiple reflections has been proposed for the reconstruction of the relative permittivity and thickness pertaining to different dielectric samples from the measurement of the reflection coefficients only. The unique advantage of this method is no requirement of measurement of any additional parameter to determine relative permittivity and thickness profile of the sample. Thus, it provides a cost-effective solution. The accuracy of this method for reconstructing the permittivity and thickness of the dielectric wall is very high and the measured error is less than 0.26% for permittivity values and 1.4% for thickness values for the most optimized reconst1ructed values. This method has been verified for different samples having different thickness and hence the optimum thickness for each sample has been determined. © 2019 URSI. All rights reserved.